2018
DOI: 10.3168/jds.2017-13946
|View full text |Cite
|
Sign up to set email alerts
|

Long-term palmitic acid supplementation interacts with parity in lactating dairy cows: Production responses, nutrient digestibility, and energy partitioning

Abstract: The objective of our study was to evaluate the effects of long-term palmitic acid (C16:0) supplementation and parity on production, nutrient digestibility, and energy partitioning of mid-lactation dairy cows. Forty mid-lactation Holstein cows (18 primiparous and 22 multiparous) were used in a block design. Cows were assigned to receive either a control diet containing no supplemental fat (CON) or a C16:0-enriched supplemented diet (PA; 1.5% diet dry matter) fed for 10 wk. Compared with CON, PA increased dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…We observed that compared with CON, PA treatments reduced the digestibility of 16-carbon FA and total FA. Although Rico et al (2014a) reported that feeding a highly enriched C16:0 supplement had positive effects on 16-carbon and total FA digestibilities of low-producing cows, other studies with high-producing cows have observed reductions in FA digestibility when feeding similar supplements (de Souza et al, 2017;de Souza and Lock, 2018a). In a recent meta-analysis, Boerman et al (2015) observed no reduction in FA digestibility when the duodenal flow of C16:0 increased up to 500 g/d, whereas increasing the duodenal flow of C18:0 to the same level reduced FA digestibility.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We observed that compared with CON, PA treatments reduced the digestibility of 16-carbon FA and total FA. Although Rico et al (2014a) reported that feeding a highly enriched C16:0 supplement had positive effects on 16-carbon and total FA digestibilities of low-producing cows, other studies with high-producing cows have observed reductions in FA digestibility when feeding similar supplements (de Souza et al, 2017;de Souza and Lock, 2018a). In a recent meta-analysis, Boerman et al (2015) observed no reduction in FA digestibility when the duodenal flow of C16:0 increased up to 500 g/d, whereas increasing the duodenal flow of C18:0 to the same level reduced FA digestibility.…”
Section: Discussionmentioning
confidence: 98%
“…This FA has been reported to increase milk yield, milk fat concentration and yield, and the efficiency of milk production compared with a control diet (Mosley et al, 2007;Lock et al, 2013;de Souza et al, 2017) and with other FA supplements (Rico et al, 2014a,b;de Souza et al, 2018). However, variation in response to C16:0 has also been reported, with some studies reporting no effect of C16:0 supplementation on milk yield (Lock et al, 2013;Rico et al, 2014a), whereas others reported increases in milk yield (Mosley et al, 2007;Piantoni et al, 2013;de Souza and Lock, 2018a). Because the supplements described in the above-mentioned studies were similar in FA composition, understanding factors (e.g., basal diet composition, characteristics of fat supplements) that are associated with variations in production responses may allow for more precise feeding recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the differences between individual FA is crucial to determining optimal dietary FA profiles for cows. Recent research indicates that C16:0 supplementation increases milk fat concentration and yield and NDF digestibility compared with non-FA-supplemented control diets and other FA supplements (de Souza and Lock, 2018b;Western et al, 2020). Boerman et al (2017) fed increasing levels of a C18: 0 -enriched supplement (~93% C18:0) to dairy cows and observed no positive effect on production responses, which was likely associated with the pronounced decrease in total FA digestibility as FA intake increased.…”
Section: Introductionmentioning
confidence: 98%
“…Supplementing a moderately enriched PA prill (~80 to 85%) with >7% UFA has variable effects on FA digestibility. For example, 2 publications reported decreases in total FA digestibility of <5 percentage units and in C16 FA digestibility <11 percentage units de Souza and Lock, 2018), whereas Rico et al (2014a) reported increased total and C16 FA digestibility with an ~85% PA supplement. The fat supplement used in Rico et al (2014a) was assessed in the present study as stock I (93.0% PA + 4.8% UFA), which had 17.6 J/g (8.1%) lower enthalpy than stock H (96.3% PA + 0.3% UFA).…”
Section: Characterization Of Experimental and Commercial Fa Supplementsmentioning
confidence: 99%
“…Recent work has shown that supplements that are highly enriched in SA and depleted in other SFA or UFA decreased total-tract FA digestibility by over 20 percentage points (Piantoni et al, 2015;Boerman et al, 2017) and those very highly enriched in PA decreased 16-carbon FA digestibility over 17 percentage units (Piantoni et al, 2013). Studies feeding moderately enriched PA (80 to 85%) reported decreases of less than 5 percentage points in total-tract digestibility (de Souza et al, 2017;de Souza and Lock, 2018), and one publication reported an increase in FA digestibility compared with a no-fat control diet (Rico et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%